Toward an Exergue on the Future of Différance. Issue 1 (May 2020) - Ross, Daniel
Abstract : In Of Grammatology, Derrida discusses Leroi-Gourhan in relating différance to memory, the 'program', and the history of life. In Technics and Time, 1, Stiegler argues that Derrida failed to draw all the philosophical implications of linking différance to the questions of life and retention. Derrida returned to the life sciences in 1975, in a seminar not published in its entirety until 2019. There, Derrida attempts to deconstruct the geneticist François Jacob's account of the 'logic of life', but Derrida's analysis of different kinds of memory and programs seems confused, suggesting that the Derridean text remains haunted by the deficiencies of his earlier reading of Leroi-Gourhan. Later in the seminar, Derrida shows foresight concerning the problems arising from seeing the genetic molecule as akin to a computer program, despite Jacob making this link via Schrödinger and Wiener's discussions of negentropy. When Derrida turns to a reading of Freud and libidinal energy, however, he 'assumes' a reading of Laplanche but ignores the latter's critique of Freud's own preoccupations with the second law of thermodynamics. The limitations of Derrida's attempts to bring deconstruction together with scientific understanding expose the need for the kind of 'organological' and 'neganthropological' approach that Stiegler will ultimately pursue.